PENGARUH SKOLIOSIS TERHADAP TIMBULNNYA OSTEOARTRITIS LUTUT SEKUNDER PADA ATLET DI RUMAH SAKIT OLAHRAGA NASIONAL CIBUBUR PERIODE JULI 2013 -APRIL 2014 - Ryan Gamma Andiraldi Putra, (2014)
Osteoarthritis on the knee can caused by scoliosis. The purpose of this study is to find out the influence of scoliosis caused secondary osteoarthritis on the knee. This research use an analytic cross-sectional design. The total sample of 92 athletes scoliosis taken by simple random sampling technique. The data were analyzing with Chi-square test, Fisher and Prevalence Ratio. The results show that there were influences on the incidence of scoliosis towards secondary osteoarthritis on the knee in athletes at the National Sports Hospital. Based on the criteria in the Cobbs angle had the results (p = 0.022 (p <0.05)), moderate Cobbs angle degree were 7.5 times more at risk of causing secondary osteoarthritis on the knee than a mild degree. The other hand shape of the curve scoliosis had results (p = 0.038 (p <0.05)), the shape of the S curve scoliosis 3.2 times more at risk of causing secondary osteoarthritis on the knee than the curve C. It had to be concluded that there was influence between scoliosis towards incidence of secondary osteoarthritis on the knee.